2020
DOI: 10.1177/0192623320968079
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Toxicology and Biocompatibility Program Supporting Clinical Development and Registration of the Port Delivery System With Ranibizumab for Neovascular Age-Related Macular Degeneration

Abstract: The Port Delivery System with ranibizumab (PDS) is an investigational drug delivery system designed to provide continuous intravitreal release of ranibizumab for extended durations. The PDS consists of a permanent, surgically placed, refillable intraocular implant; a customized formulation of ranibizumab; and ancillary devices to support surgery and refill procedures. A toxicology program was conducted to evaluate the ocular toxicology and biocompatibility of the PDS to support its clinical development program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Both in vitro and in vivo biocompatibility tests showed that PDS implant was non-cytotoxic, non-genotoxic, non-sensitizing, and non-irritating. 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in vitro and in vivo biocompatibility tests showed that PDS implant was non-cytotoxic, non-genotoxic, non-sensitizing, and non-irritating. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Toxicology and biocompatibility analysis of the PDS implant both in vitro and in vivo has shown that it is non-toxic, non-sensitizing, and non-inflammatory. 35 Long-term stability of ranibizumab under physiologic conditions was also favorable for ranibizumab when compared to bevacizumab and aflibercept. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The PDS implant is surgically placed at the pars plana and is intentionally designed to be biocompatible, permanent, and durable. The implant and extracts from the implant and ancillary devices have been determined to be nongenotoxic, noncytotoxic, nonsensitizing, and nonirritating (Bantseev et al., 2021 ). The drug reservoir and RCE reside within the vitreous, whereas the septum remains accessible under the conjunctiva and Tenon’s capsule for minimally invasive in-clinic refill-exchanges.…”
Section: The Pds Implant and Ancillary Devicesmentioning
confidence: 99%
“…Plastic embedding is not recommended for the whole eye in these situations, as the sections are somewhat thicker than those usually examined. 54…”
Section: General Points To Considermentioning
confidence: 99%